(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Human resource activities extend beyond hiring and orientation. With the advent of HR analytics, the human capital industry has seen a profound transformation. Employer turnover analysis, talent supply chain optimization, decision-maker insight extraction, and other tasks are all accomplished by organisations using HR analytics.